1983
DOI: 10.2170/jjphysiol.33.41
|View full text |Cite
|
Sign up to set email alerts
|

Regional blood flow in conscious spontaneously hypertensive rats.

Abstract: In spontaneously hypertensive and normal control rats in the conscious state, blood flow was observed in the carotid artery, superior mesenteric artery, renal artery, and terminal aorta with a chronically implanted electromagnetic flow probe. At rest, flow per body weight was not different between the two groups except at the terminal aorta where it was significantly smaller in hypertensive rats (P<0.05).Regional peripheral resistance was higher in hypertensive rats than in normal rats in all the four arteries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The NE levels and the TH activities in the abdominal aor ta and the mesenteric artery of SHR were significantly higher than those of WKY. Iriuchijima (6) reported that the elevation of the SHR's vascular resistance is not uniformly observed over the whole body, and it is especial ly marked in the abdominal aorta and the mesenteric ar tery. The vascular resistance of these arteries of SHR was about 50% greater than that of normotensive rats (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NE levels and the TH activities in the abdominal aor ta and the mesenteric artery of SHR were significantly higher than those of WKY. Iriuchijima (6) reported that the elevation of the SHR's vascular resistance is not uniformly observed over the whole body, and it is especial ly marked in the abdominal aorta and the mesenteric ar tery. The vascular resistance of these arteries of SHR was about 50% greater than that of normotensive rats (18).…”
Section: Discussionmentioning
confidence: 99%
“…Judy et al (5) reported that sympathetic nerve activity is increased in the nerves distributing to the abdominal regions in SHR. Iriuchijima (6) reported that the high vascular resistance in hindquarter and mesenteric arteries of SHR is maintained by an elevated sympathetic tone. Therefore, increased sympathetic tone or sympa thetic nerve activity in arteries of these regions may con tribute to hypertension in SHR.…”
mentioning
confidence: 99%
“…This result suggests that, in the conscious state, sympathetic vasoconstrictor tone in resistance vessels of the hindquarter area is immaterial in normal rats in contrast to spontaneously hypertensive rats, in which hindquarter vasoconstrictor tone is important to their hypertension (IRIUcHIJIMA, 1983a).…”
mentioning
confidence: 95%
“…It has been demonstrated by this method that, in spontaneously hypertensive rats (SHR, OKAMOTO and AOKI, 1963) and one-clip, two-kidney renovascular hypertensive rats, elevation of peripheral vascular resistance is not uniform over the entire body. In SHR, elevation of resistance is especially marked in the hindquarters (IRIUCHIJIMA, 1983). In one-clip, two-kidney rats, the area with marked resistance elevation is the splanchnic bed supplied by the superior mesenteric artery (TERANISHI and IRIUCHIJIMA, 1985).…”
mentioning
confidence: 99%